(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Temples are the most important centers of the society. They are functioning with liberal donations of the devotees. Cattles of the main sources of income to the temples. For lighting perpetual lamp, the necessary ghee is got from the cattle. The shepherds mostly depending upon the cattle rearing. The inscriptions from Iluppur Taluk number of evidences were collected which denote cattle donations. In this paper the impact of cattle donations and their social background are discuss the elaborately.